An investigation of the origin and significance of bilateral symmetry of the pronuclear zygote in the mouse. - Gardner, R; Davies, T (2006)
BACKGROUND: Preliminary observations revealed that advanced zygotes of the PO strain mouse are often bilaterally symmetrical, and suggested that both the plane of first cleavage and features of the blastocyst bear a consistent relationship to the zygote's bilateral plane. METHODS: Spaced oil drops were injected into the zona pellucida to delineate the bilateral plane in pronuclear zygotes, and a distinct cluster of drops then placed over the second polar body. Such non-invasive marking was combined with gelation of the perivitelline space to prevent rotation of the zygotes within the zona pellucida. RESULTS: Nearly two-thirds of advanced pronuclear stage zygotes were bilaterally symmetrical and, regardless of whether first cleavage was meridional, it was almost invariably orthogonal to the bilateral plane. Moreover, both the axis of polarity and bilateral plane of the blastocyst bore a consistent relationship to the zygote's bilateral plane. Haploid parthenotes also exhibited bilateral symmetry, although in the absence of fertilization, first cleavage was less consistently orthogonal to the bilateral plane. CONCLUSIONS: Bilateral symmetry may be an intrinsic property of the oocyte that is induced by its activation and, from the reproducible way it maps on both the 2-cell conceptus and blastocyst, seems to play a role in early patterning.